1977
DOI: 10.1016/0002-9610(77)90546-3
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal lavage

Abstract: The concept of lavage as an effective means for detecting intraperitoneal injury secondary to trauma has been adequately demonstrated. The value of peritoneal lavage is especially reflected in the statistics reporting approximately 20 per cent incidence of unnecessary celiotomies when physical examination findings alone are used; whereas the number of false-positives and false-negatives may be lowered significantly. Not only does peritoneal lavage decrease the number of unnecessary celiotomies, but it also pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is usual for 700-800 ml to be returned. (8) The flask is then inspected for blood-staining. If it is heavily blood-stained such that one cannot read newsprint through the flask, this is a positive lavage result.…”
Section: Peritoneal Lavagementioning
confidence: 99%
See 1 more Smart Citation
“…It is usual for 700-800 ml to be returned. (8) The flask is then inspected for blood-staining. If it is heavily blood-stained such that one cannot read newsprint through the flask, this is a positive lavage result.…”
Section: Peritoneal Lavagementioning
confidence: 99%
“…The initial clinical assessment of the patient who has sustained blunt abdominal trauma and the subsequent decision whether or not to proceed to early laparotomy is often difficult, particularly if there are associated injuries . '- 8 Four quadrant needle paracentesis has been employed as a diagnostic aid, but suffers from a significant number of false positive and false negative results ' -I 1 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Peritoneal lavage consists of using variable amounts of a liquid, usually normal saline, in order to washout the peritoneal cavity. 5 It is believed that peritoneal lavage can washout the microorganisms, as well as inflammatory cytokines and blood from the peritoneal cavity, which can improve the inflammatory state and decrease the growth rate of the bacteria. 6 It is now reported that Gentamicin-Clindamycin Lavage (GCL) after elective colorectal surgeries can improve survival in patients with colorectal tumors.…”
Section: Introductionmentioning
confidence: 99%